(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
For any thriving sustainable planning, we need a contextual site specific holistic approach with the economical, social, ecological, spatial and environmental along with detail investigation of the climatic, geographical, cultural and landscape studies. The detail environmental factors and planning parameters to be considered by the architects and planners for any development related to the three major environments like the coastal, hilly and desert are explained in detail. The importances of landscape planning and design in the three different ecologically bio diversified areas are further highlighted to achieve sustainability. Other planning parameters like energy efficiency, selection of appropriate materials, water conservation etc. for achieving sustainable building design in an urban area has been discussed. The different methods and various models are discussed to pave the way for achieving sustainable development such as the multidisciplinary and transdisciplinary approaches. A New Planning Model has been suggested by integrating the techniques and methods of various ecological landscape planning approaches.